The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1590/s0074-02761991000600029
|View full text |Cite
|
Sign up to set email alerts
|

Enterolobin induces rat paw oedema independently of PAF-acether

Abstract: The potential participation of PAF-acether (PAF) on the paw oedema triggered by enterolobin was investigated. Intraplantar injections of enterolobin )5-20 µg/paw) yielded a dose response curve for edema which appeared after 30 min, peaked in the interval between 2-4 h and faded after 24h. The pre-treatment with BN 52021, but not with other PAF antagonists such as PCA 4248 or WEB 2086, significantly blocked enterolobin-induced oedema. To clarify better the discrepant results obtained with the PAF antagonists, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In vitro proteolysis studies showed that Entrolobin is resistant to the digestion by larval gut enzymes of C. maculatus (Sousa et al, 1993). Enterolobin also induces inflammation upon injection in rats (Castro Faria Neto et al, 1991). Similar to other poreforming toxins, the oligomerization of enterolobin is promoted by low pH and high ionic strength (Fontes et al, 1997).…”
Section: Pore-forming Toxinsmentioning
confidence: 99%
“…In vitro proteolysis studies showed that Entrolobin is resistant to the digestion by larval gut enzymes of C. maculatus (Sousa et al, 1993). Enterolobin also induces inflammation upon injection in rats (Castro Faria Neto et al, 1991). Similar to other poreforming toxins, the oligomerization of enterolobin is promoted by low pH and high ionic strength (Fontes et al, 1997).…”
Section: Pore-forming Toxinsmentioning
confidence: 99%
“…Enterolobin was first purified by Sousa et al in 1989 [102]. Since enterolobin harbours insecticidal activities against larvae of the brucid Calosobruchus macullatus [102], and causes inflammation upon injection in rats [104], it may serve as a defence against potential herbivores. Three known outbreaks of intoxication have also been caused by E. contortisiliquum pods [105] consumed by cattle, leading to anorexia, depression, photosensitization, and abortion.…”
Section: Enterolobin From Seeds Of Enterolobium Contortisiliquum (Eukmentioning
confidence: 99%